An Investigation of the Electrochemical Behaviors of M0.85Se (M=Ni, Co) Materials for Alkaline Aqueous Battery. Issue 16 (4th December 2018) - Zhu, Yirong; Yun, Xiaoru; Li, Jingying; Xiang, Kaixiong; Xiao, Li; Chen, Han; Chen, Xianhong
Abstract : Metal selenides, as a new class of alkaline aqueous battery materials, have attracted more researchers' attention in recent years. In this work, the M0.85 Se (M=Ni, Co) materials with different morphologies are successfully synthesized via a two-step hydrothermal method by using different solvents. The effects of solvents and transition metals on structure, morphology, specific surface area and pore structure and electrochemical properties of the products are systematically explored. The electrochemical measurements reveal that the Ni0.85 Se products prepared by H2 O and ethanol exhibit higher specific capacity (83.8 and 65.3 mAh g −1 at 1 A g −1 ), whereas the Co0.85 Se products prepared by H2 O and ethanol display better rate capability (75.1 and 69.0% of capacity retention rate at 50 A g −1 ) and cycling stability (97.6 and 94.5% of capacity retention at 5 A g −1 after 2000 cycles), respectively. The different electrochemical properties can be ascribed to the fact that the Ni0.85 Se electrodes show diffusion-controlled faradaic chracteristic while the Co0.85 Se electrodes present mixed behavior of diffusion-controlled faradaic and capacitive feature. Such work is of fundamental importance and it provides a valuable reference for the tailoring of these different properties by the use of various solvents and transition metals.